A high-performance rare earth composite calcium carbide furnace cover refractory castable and preparation method thereof

Through the combination of rare earth oxides and materials such as silicon oxide and high alumina raw materials, the mechanical strength and thermal shock resistance of the castable material in the catheter furnace cover are improved, and the peeling and compactness of the existing castable material under extremely cold and extremely hot conditions is solved. Poor performance problems extend service life and reduce maintenance frequency.

CN119080483BActive Publication Date: 2025-01-07BAOTOU ANDESHANAI NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411582943.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-07
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The castable material of the existing calcium carbide furnace cover is easily peeled off and crusted under extremely cold and extremely hot conditions, and the silicon carbide refractory castable material has poor density and low strength, resulting in a short service life and high maintenance frequency.

Method used

High-performance rare earth composite castables using rare earth oxides and silicon oxide, high-aluminum raw materials brown corundum, aluminate cement and clay additives, and new components are formed through the reaction of rare earth oxides and brown corundum. Activate the system components to improve sintering density and strength.

Benefits of technology

On the basis of ensuring no peeling and no scalding, the mechanical strength and thermal shock resistance of the furnace cover are improved, the service time is extended, and the maintenance frequency is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119080483B_ABST
    Figure CN119080483B_ABST
Patent Text Reader

Abstract

The invention provides a high-performance rare earth composite calcium carbide furnace cover refractory castable and a preparation method thereof. The castable comprises the following raw materials in parts by weight: 100 parts of casting mixture, 0.5-3 parts of rare earth oxide, 0.1-0.2 parts of explosion-proof fiber, 0.1-0.3 parts of water reducer and 5-8 parts of water; wherein the casting mixture is composed of the following raw materials in parts by weight: 50-68 parts of brown corundum, 15-20 parts of mullite, 5-10 parts of aluminate cement, 4-7 parts of alumina micropowder, 4-6 parts of silicon oxide micropowder, 3-5 parts of clay additive, and 1-2 parts of chromium oxide green. The preparation method comprises: sieving brown corundum and mullite to the required particle size; weighing the above raw materials and their proportions, and then putting all the raw materials except water into a mixer and stirring for 10-20 minutes to fully mix the materials; after the materials are stirred evenly, slowly adding 5-8 parts of water and stirring until the castable is in a viscous state. The refractory castable provided by the invention improves the mechanical strength and thermal shock resistance of the furnace cover castable while ensuring that the furnace cover castable does not peel off or form a skin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of castables, and in particular relates to a high-performance rare earth composite calcium carbide furnace cover refractory castable and a preparation method thereof. Background Art

[0002] my country is a major producer of calcium carbide. As the main equipment in the production process of calcium carbide, calcium carbide furnaces can be divided into three categories according to their structure: open, semi-closed and fully closed. Open calcium carbide furnaces have been completely closed due to their high environmental pollution and high energy consumption. With the needs of economic development and energy conservation and emission reduction, semi-closed calcium carbide furnaces are also being gradually eliminated. Closed calcium carbide furnaces are the environmentally friendly calcium carbide furnaces mainly promoted by the country. The furnace cover is one of the core equipment of the closed calcium carbide furnace. The furnace cover of the calcium carbide furnace is an important part that determines the efficiency of sealing and collecting furnace gas. Its normal operating temperature range is -30~400℃. In emergencies (turning over calcium carbide), the temperature can rise to less than 1500℃. During use, the furnace cover is prone to smoke and fire. It is severely eroded by smoke and hot air. If the furnace cover is not sealed well, a large amount of gas will leak. Therefore, the refractory castables used for the furnace cover must be gas erosion-resistant, wear-resistant, and erosion-resistant, and the castables should be prevented from falling off, and the bonding performance between the castables and the anchors should be enhanced. Small calcium carbide furnace covers mostly use high-aluminum, low-cement castables, because low-cement castables have low calcium content, require less water during construction, are easy to bake and have good strength, but there are also problems of peeling and crusting caused by extreme cold and heat, which shortens the service life of the furnace cover. At present, large calcium carbide furnace covers mostly use silicon carbide castables. One of the major advantages of silicon carbide refractory castables is anti-scaling, but it also has obvious disadvantages. Silicon carbide has poor water solubility and poor fluidity in water-based castables, resulting in poor density of silicon carbide refractory castables. In addition, silicon carbide materials will shrink significantly during the sintering process, which is not conducive to the fixation of the castable on the anchor, and silicon carbide refractory castables are difficult to achieve high strength, shortening the use time of the furnace cover and increasing the frequency of maintenance. Summary of the invention

[0003] In view of the deficiencies of the above-mentioned prior art, the present invention provides a high-performance rare earth composite calcium carbide furnace cover refractory castable and a preparation method thereof. The castable combines rare earth oxides with a refractory castable containing silicon oxide, high-aluminum raw material brown corundum, aluminate cement and clay additives, thereby overcoming the shortcomings of existing calcium carbide furnace cover castables, and improving its mechanical strength and thermal shock resistance while ensuring that the furnace cover castable does not peel or form a skin, thereby extending the service life of the furnace cover and reducing the maintenance frequency.

[0004] Specifically, the first aspect of the present invention provides a high-performance rare earth composite calcium carbide furnace cover refractory castable, comprising the following raw materials in parts by weight: 100 parts of casting mixture, 0.5-3 parts of rare earth oxide, 0.1-0.2 parts of explosion-proof fiber, 0.1-0.3 parts of water reducer and 5-8 parts of water;

[0005] The casting mixture is composed of the following raw materials in parts by weight: 50-68 parts of brown corundum, 15-20 parts of mullite, 5-10 parts of aluminate cement, 4-7 parts of alumina powder, 4-6 parts of silicon oxide powder, 3-5 parts of clay additive, and 1-2 parts of chromium oxide green.

[0006] As a further illustration of the present invention, in the brown corundum raw material, the raw material with a particle size of 5-8 mm accounts for 10wt%-30wt% of the total amount of brown corundum, the raw material with a particle size of 3-5 mm accounts for 30wt%-35wt% of the total amount of brown corundum, the raw material with a particle size of 1-3 mm accounts for 15wt%-20wt% of the total amount of brown corundum, the raw material with a particle size of 0-1 mm accounts for 15wt%-20wt% of the total amount of brown corundum, and the raw material with a particle size of 200 mesh accounts for 10wt%-15wt% of the total amount of brown corundum.

[0007] As a further illustration of the present invention, in the mullite raw material, the raw material with a particle size of 1-3 mm accounts for 30wt%-35wt% of the total amount of mullite, the raw material with a particle size of 0-1 mm accounts for 30wt%-35wt% of the total amount of mullite, and the raw material with a particle size of 200 mesh accounts for 30wt%-40wt% of the total amount of mullite.

[0008] As a further illustration of the present invention, the aluminate cement model is one of CA50, CA70, and CA80, or a mixture of several of them.

[0009] As a further illustration of the present invention, the rare earth oxide is lanthanum oxide, cerium oxide or a mixture of both.

[0010] As a further illustration of the present invention, the clay additive is bentonite, Guangxi white mud or a mixture of both.

[0011] As a further illustration of the present invention, the water reducing agent is one or a mixture of several of sodium tripolyphosphate, sodium lignin sulfonate, sodium hexametaphosphate, and calcium lignin sulfonate.

[0012] The second aspect of the present invention provides a method for preparing the above-mentioned high-performance rare earth composite calcium carbide furnace cover refractory castable, comprising the following steps:

[0013] (1) Screen brown corundum and mullite to the required particle size and package them for later use;

[0014] (2) Weigh the above raw materials and their proportions, then put all the raw materials except water into a blender and stir for 10 to 20 minutes to fully mix the materials;

[0015] (3) After the materials are stirred evenly, continue to turn on the mixer and slowly add 5 to 8 parts of water. Stir until the castable becomes viscous to obtain the refractory castable for the calcium carbide furnace cover.

[0016] As a further illustration of the present invention, step (1) specifically includes:

[0017] Place brown corundum and mullite in an electric heating blast drying oven at 90°C to 110°C to dry them;

[0018] The brown corundum is passed through 5~8mm, 3~5mm, 1~3mm, 0~1mm and 200 mesh sieves respectively, and the sieve residue is less than 5%; the mullite is passed through 1~3mm, 0~1mm and 200 mesh sieves respectively, and the sieve residue is less than 5%; and they are packaged for use.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] The high-performance rare earth composite calcium carbide furnace cover refractory castable provided by the present invention combines rare earth oxides with refractory castables containing silicon oxide, high-aluminum raw material brown corundum, aluminate cement and clay additives, etc., overcoming the shortcomings of existing calcium carbide furnace cover castables. While ensuring that the furnace cover castable does not peel off or form a skin, its mechanical strength and thermal shock resistance are improved, thereby extending the service life of the furnace cover and reducing the maintenance frequency. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention provides a preparation flow chart of the high-performance rare earth composite calcium carbide furnace cover refractory castable. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Small calcium carbide furnace covers mostly use high-aluminum, low-cement castables, because low-cement castables have low calcium content, require less water during construction, are easy to bake and have good strength, but there are also problems of peeling and crusting caused by extreme cold and heat, which shortens the service life of the furnace cover. At present, large calcium carbide furnace covers mostly use silicon carbide castables. One of the major advantages of silicon carbide refractory castables is anti-scaling, but it also has obvious disadvantages. Silicon carbide has poor water solubility and poor fluidity in water-based castables, resulting in poor density of silicon carbide refractory castables. In addition, silicon carbide materials will shrink significantly during the sintering process, which is not conducive to the fixation of the castable on the anchor, and silicon carbide refractory castables are difficult to achieve high strength, shortening the use time of the furnace cover and increasing the frequency of maintenance.

[0024] Based on the above technical problems, the present invention provides a high-performance rare earth composite calcium carbide furnace cover refractory castable, comprising the following raw materials in parts by weight: 100 parts of casting mixture, 0.5-3 parts of rare earth oxide, 0.1-0.2 parts of explosion-proof fiber, 0.1-0.3 parts of water reducer and 5-8 parts of water; wherein, the casting mixture is composed of the following raw materials in parts by weight: 50-68 parts of brown corundum, 15-20 parts of mullite, 5-10 parts of alumina cement, 4-7 parts of aluminum oxide powder, 4-6 parts of silicon oxide powder, 3-5 parts of clay additive, and 1-2 parts of chromium oxide green.

[0025] Among them, in the brown corundum raw materials, the raw materials with a particle size of 5~8mm account for 10wt%~30wt% of the total amount of brown corundum, the raw materials with a particle size of 3~5mm account for 30wt%~35wt% of the total amount of brown corundum, the raw materials with a particle size of 1~3mm account for 15wt%~20wt% of the total amount of brown corundum, the raw materials with a particle size of 0~1mm account for 15wt%~20wt% of the total amount of brown corundum, and the raw materials with a particle size of 200 mesh account for 10wt%~15wt% of the total amount of brown corundum; the alumina content in brown corundum is ≥95%.

[0026] Among them, in the mullite raw materials, the raw materials with a particle size of 1~3mm account for 30wt%~35wt% of the total amount of mullite, the raw materials with a particle size of 0~1mm account for 30wt%~35wt% of the total amount of mullite, and the raw materials with a particle size of 200 mesh account for 30wt%~40wt% of the total amount of mullite; the alumina content in mullite is ≥60%.

[0027] In an achievable manner, the type of aluminate cement is one or a mixture of CA50, CA70, and CA80. The rare earth oxide is one or a mixture of lanthanum oxide and cerium oxide. The clay additive is one or a mixture of bentonite and Guangxi white mud. The water reducer is one or a mixture of sodium tripolyphosphate, sodium lignin sulfonate, sodium hexametaphosphate, and calcium lignin sulfonate.

[0028] The method for preparing the high-performance rare earth composite calcium carbide furnace cover refractory castable comprises the following steps:

[0029] (1) Screen brown corundum and mullite to the required particle size and package them for later use;

[0030] (2) Weigh the above raw materials and their proportions, then put all the raw materials except water into a blender and stir for 10 to 20 minutes to fully mix the materials;

[0031] (3) After the materials are stirred evenly, continue to turn on the mixer and slowly add 5 to 8 parts of water. Stir until the castable becomes viscous to obtain the refractory castable for the calcium carbide furnace cover.

[0032] Wherein, step (1) specifically includes:

[0033] Place brown corundum and mullite in an electric heating blast drying oven at 90°C to 110°C to dry them;

[0034] The brown corundum is passed through 5~8mm, 3~5mm, 1~3mm, 0~1mm and 200 mesh sieves respectively, and the sieve residue is less than 5%; the mullite is passed through 1~3mm, 0~1mm and 200 mesh sieves respectively, and the sieve residue is less than 5%; and they are packaged for use.

[0035] Rare earth atoms have a compact electron layer structure, with variable valence, large radius, active chemical properties, etc., and the inner 4f electrons of rare earth elements are shielded by the outer 5s and 5p electrons, which has a localization effect. The outermost electrons that determine the properties of the element are arranged in 4f and 5d to form a conduction band. The localization and incomplete filling of 4f electrons give rare earths unique optical, magnetic and oxygen storage and release properties, and the melting point of rare earth oxides is as high as 2000℃ and is not easy to volatilize. The present invention utilizes the chemical properties of rare earth elements such as chemical activity and large ion radius to add them to refractory castables. After high-temperature sintering, the rare earth elements react with SiO2 in the refractory castables ((La, Ce)2O3+SiO2→(La, Ce)2·2SiO2) to generate new components (LaCe)2·2SiO2 or La2O3·SiO2. This reaction is beneficial to the activation of alumina components in the system, and allows the aluminum-silicon ratio in the product obtained by high-temperature sintering of the castable to reach the chemical composition of mullite, thereby promoting the development and growth of mullite crystals in the product. In addition, the low-viscosity liquid phase formed by the above reaction is beneficial to the sintering of the material, improving the density and strength of the material, promoting the sintering of the refractory castable, and then improving the density of the refractory castable, and ultimately improving the density and strength of the product simultaneously.

[0036] The rare earth oxides in the present invention can interact with the high-aluminum raw material brown corundum in the system. Since the radius of rare earth ions is much larger than that of aluminum ions, it is difficult to form a solid solution with aluminum oxide, so they mainly exist on the grain boundaries. Due to the large volume of the rare earth ions themselves, the migration resistance in the structure is large, and the migration of other ions is also hindered, which reduces the grain boundary migration rate, inhibits grain growth, and is conducive to the formation of a dense structure, thereby improving the crystallization state of the high-aluminum composite material, reducing the defect rate of the material crystal, and improving the corrosion resistance of the material, thereby improving the microstructure and high-temperature structural performance of the castable. The molded product can resist thermal shock times of 50 to 60 times in a 1100°C water-cooled cycle, indicating that the castable can still guarantee its performance during the use of the calcium carbide furnace cover even if the calcium carbide is turned over many times.

[0037] The invention adds aluminate cement and clay additives, the castable has high viscosity, and the linear change rate after molding is less than 0.3%, which can ensure that the castable is directly bonded to the anchor of the calcium carbide furnace cover without falling off.

[0038] In summary, the high-performance rare earth composite calcium carbide furnace cover refractory castable prepared by the present invention has the characteristics of high mechanical strength, high density, good thermal shock resistance, no skinning, no peeling, good corrosion resistance and long service life.

[0039] The present invention will be further described below in conjunction with specific embodiments:

[0040] Table 1 and Table 2 below are raw materials and equipment information tables used in the examples and comparative examples of the present invention.

[0041] Table 1 Raw material composition

[0042] raw material Main Ingredients Brown corundum <![CDATA[Weight content: Al2O3: 95%, the oxides of the remaining components account for 5%]]> Mullite <![CDATA[Weight content: Al2O3: 60%, the oxides of the remaining components account for 40%]]> Silicon oxide powder <![CDATA[Weight content: SiO2: 96%, the oxides of the remaining components account for 4%]]> Alumina powder <![CDATA[Weight content: Al2O3: 99%, the oxides of the remaining components account for 1%]]> Guangxi white clay <![CDATA[Weight content: SiO2: 50%, Al2O3: 20%, Fe2O3: 1.33]]> Bentonite Weight content: montmorillonite 74%, other oxides account for 26% Lanthanum Cerium Oxide <![CDATA[Weight content: 99% La2O3, oxides of the remaining components account for 1% or 99% CeO2, oxides of the remaining components account for 1%]]> CA70 <![CDATA[Weight content: Al2O3: 75%, SiO2: 1%, the oxides of the remaining components account for 24%]]>

[0043] Table 2 Equipment information table

[0044] name factory model Bending and compression testing machine Sinosteel Luoyang Refractory Research Institute Co., Ltd. CCS-600 / 10P Stomata and body density measuring instrument Sinosteel Luoyang Refractory Research Institute Co., Ltd. XQK-02 High temperature reburning furnace Sinosteel Luoyang Refractory Research Institute Co., Ltd. CSL-17-18Y Commercial mixer three functions Tianjin Zhonghuan Experimental Electric Furnace Co., Ltd. ADYF-059 Electric blast drying oven Beijing Yongguangming Medical Instrument Co., Ltd. 101-1ABS Mortar specimen forming and compaction table Shanghai Guangdi Instrument Equipment Co., Ltd. ZT-96 Example 1

[0045] Table 3 Components and dosages of Example 1

[0046] Raw material name Particle size (mm) Weight Remark Brown corundum 5~8 16 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 3~5 20 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 1~3 10 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 0~1 10 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 200 mesh 8 <![CDATA[The Al2O3 content is 95% <!-- 4 -->]]> Mullite 1~3 6 <![CDATA[The Al2O3 content is 60%]]> Mullite 0~1 6 <![CDATA[The Al2O3 content is 60%]]> Mullite 200 mesh 7 <![CDATA[The Al2O3 content is 60%]]> CA50 6 Alumina powder 4 Silicon oxide powder 4 Lanthanum Oxide 0.5 Bentonite 3 Chrome Oxide Green 1 Explosion-proof fiber 0.15 Sodium Hexametaphosphate 0.2

[0047] The method for preparing a sample block of a high-performance rare earth composite calcium carbide furnace cover refractory castable of the present embodiment comprises the following steps:

[0048] (1) Place brown corundum and mullite in an electric blast drying oven at 110°C to dry them; then pass the brown corundum through 5~8mm, 3~5mm, 1~3mm, 0~1mm and 200 mesh sieves respectively, with the sieve residue less than 5%; pass the mullite through 1~3mm, 0~1mm and 200 mesh sieves respectively, with the sieve residue less than 5%; package for standby use;

[0049] (2) Weigh the raw materials and their proportions in the above table, then put all the raw materials into a blender and stir for 15 minutes to fully mix the materials;

[0050] (3) After the materials are stirred evenly, continue to turn on the mixer and slowly add 6 parts by weight of water. After stirring until the castable becomes viscous, inject it into a 160mm×40mm×40mm mold and vibrate on a compaction table for 2 minutes to remove bubbles and compact the material.

[0051] (4) The castable obtained in step (3) is naturally cured for 24 hours and then demolded, and then baked in an oven at 110°C for 24 hours. After baking, three specimens are taken and heated at 1500°C for 3 hours, kept warm for 3 hours, and taken out as the furnace temperature naturally cools to room temperature to obtain a sample of high-performance rare earth composite calcium carbide furnace cover refractory castable. Example 2

[0052] Table 4 Components and contents of Example 2

[0053] Raw material name Particle size (mm) Weight percentage (%) Remark Brown corundum 5~8 16 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 3~5 20 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 1~3 10 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 0~1 10 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 200 mesh 8 <![CDATA[The Al2O3 content is 95%]]> Mullite 1~3 6 <![CDATA[The Al2O3 content is 60%]]> Mullite 0~1 6 <![CDATA[The Al2O3 content is 60%]]> Mullite 200 mesh 7 <![CDATA[The Al2O3 content is 60%]]> CA70 6 Alumina powder 4 Silicon oxide powder 4 Lanthanum Oxide 1.0 Bentonite 3 Chrome Oxide Green 1 Explosion-proof fiber 0.15 Sodium lignin sulfonate 0.2

[0054] The method for preparing a sample block of a high-performance rare earth composite calcium carbide furnace cover refractory castable of the present embodiment comprises the following steps:

[0055] (1) Place brown corundum and mullite in an electric blast drying oven at 110°C to dry them; then pass the brown corundum through 5~8mm, 3~5mm, 1~3mm, 0~1mm and 200 mesh sieves respectively, with the sieve residue less than 5%; pass the mullite through 1~3mm, 0~1mm and 200 mesh sieves respectively, with the sieve residue less than 5%; package for standby use;

[0056] (2) Weigh the raw materials and their proportions in the above table, then put all the raw materials into a blender and stir for 16 minutes to fully mix the materials;

[0057] (3) After the materials are stirred evenly, continue to turn on the mixer and slowly add 5 parts by weight of water. After stirring until the castable becomes viscous, inject it into a 160mm×40mm×40mm mold and vibrate on a compaction table for 2 minutes to remove bubbles and compact the material.

[0058] (4) The castable obtained in step (3) is naturally cured for 24 hours and then demolded, and then baked in an oven at 110°C for 24 hours. After baking, three specimens are taken and heated at 1500°C for 3 hours, kept warm for 3 hours, and taken out as the furnace temperature naturally cools to room temperature to obtain a sample of high-performance rare earth composite calcium carbide furnace cover refractory castable. Example 3

[0059] Table 5 Components and contents of Example 3

[0060] Raw material name Particle size (mm) Weight percentage (%) Remark Brown corundum 5~8 16 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 3~5 20 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 1~3 10 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 0~1 10 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 200 mesh 8 <![CDATA[The Al2O3 content is 95%]]> Mullite 1~3 6 <![CDATA[The Al2O3 content is 60%]]> Mullite 0~1 6 <![CDATA[The Al2O3 content is 60%]]> Mullite 200 mesh 7 <![CDATA[The Al2O3 content is 60%]]> CA70 6 Alumina powder 4 Silicon oxide powder 4 Cerium Oxide 3 Bentonite 3 Chrome Oxide Green 1 Explosion-proof fiber 0.15 Sodium tripolyphosphate 0.2

[0061] The method for preparing a sample block of a high-performance rare earth composite calcium carbide furnace cover refractory castable of the present embodiment comprises the following steps:

[0062] (1) Place brown corundum and mullite in an electric blast drying oven at 110°C to dry them; then pass the brown corundum through 5~8mm, 3~5mm, 1~3mm, 0~1mm and 200 mesh sieves respectively, with the sieve residue less than 5%; pass the mullite through 1~3mm, 0~1mm and 200 mesh sieves respectively, with the sieve residue less than 5%; package for standby use;

[0063] (2) Weigh the raw materials and their proportions in the above table, then put all the raw materials into a blender and stir for 20 minutes to fully mix the materials;

[0064] (3) After the materials are stirred evenly, continue to turn on the mixer and slowly add 8 parts by weight of water. After stirring until the castable becomes viscous, inject it into a 160mm×40mm×40mm mold and vibrate on a compaction table for 2 minutes to remove bubbles and compact the material.

[0065] (4) The castable obtained in step (3) is naturally cured for 24 hours and then demolded, and then baked in an oven at 110°C for 24 hours. After baking, three specimens are taken and heated at 1500°C for 3 hours, kept warm for 3 hours, and taken out as the furnace temperature naturally cools to room temperature to obtain a sample of high-performance rare earth composite calcium carbide furnace cover refractory castable. Example 4

[0066] Table 6 Components and contents of Example 4

[0067] Raw material name Particle size (mm) Weight percentage (%) Remark Brown corundum 5~8 10 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 3~5 15 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 1~3 10 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 0~1 10 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 200 mesh 5 <![CDATA[The Al2O3 content is 95%]]> Mullite 1~3 6 <![CDATA[The Al2O3 content is 60%]]> Mullite 0~1 6 <![CDATA[The Al2O3 content is 60%]]> Mullite 200 mesh 8 <![CDATA[The Al2O3 content is 60%]]> CA60 10 Alumina powder 7 Silicon oxide powder 6 Cerium Oxide 2.0 Guangxi white clay 5 Chrome Oxide Green 2 Explosion-proof fiber 0.1 Sodium hexametaphosphate: sodium tripolyphosphate = 1:1 0.1

[0068] The method for preparing a sample block of a high-performance rare earth composite calcium carbide furnace cover refractory castable of the present embodiment comprises the following steps:

[0069] (1) Place brown corundum and mullite in an electric blast drying oven at 110°C to dry them; then pass the brown corundum through 5~8mm, 3~5mm, 1~3mm, 0~1mm and 200 mesh sieves respectively, with the sieve residue less than 5%; pass the mullite through 1~3mm, 0~1mm and 200 mesh sieves respectively, with the sieve residue less than 5%; package for standby use;

[0070] (2) Weigh the raw materials and their proportions in the above table, then put all the raw materials into a blender and stir for 20 minutes to fully mix the materials;

[0071] (3) After the materials are stirred evenly, continue to turn on the mixer and slowly add 6 parts by weight of water. After stirring until the castable becomes viscous, inject it into a 160mm×40mm×40mm mold and vibrate on a compaction table for 2 minutes to remove bubbles and compact the material.

[0072] (4) The castable obtained in step (3) is naturally cured for 24 hours and then demolded, and then baked in an oven at 110°C for 24 hours. After baking, three specimens are taken and heated at 1500°C for 3 hours, kept warm for 3 hours, and taken out as the furnace temperature naturally cools to room temperature to obtain a sample of high-performance rare earth composite calcium carbide furnace cover refractory castable. Example 5

[0073] Table 7 Components and contents of Example 5

[0074] Raw material name Particle size (mm) Weight percentage (%) Remark Brown corundum 5~8 15 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 3~5 21 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 1~3 11 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 0~1 11 <![CDATA[The Al2O3 content is 95%]]> Brown corundum 200 mesh 10 <![CDATA[The Al2O3 content is 95%]]> Mullite 1~3 5 <![CDATA[The Al2O3 content is 60%]]> Mullite 0~1 5 <![CDATA[The Al2O3 content is 60%]]> Mullite 200 mesh 5 <![CDATA[The Al2O3 content is 60%]]> CA80 5 Alumina powder 4 Silicon oxide powder 4 Cerium Oxide 2.5 Guangxi white clay 3 Chrome Oxide Green 1 Explosion-proof fiber 0.1 Calcium lignin sulfonate 0.3

[0075] The method for preparing a sample block of a high-performance rare earth composite calcium carbide furnace cover refractory castable of the present embodiment comprises the following steps:

[0076] (1) Place brown corundum and mullite in an electric blast drying oven at 110°C to dry them; then pass the brown corundum through 5~8mm, 3~5mm, 1~3mm, 0~1mm and 200 mesh sieves respectively, with the sieve residue less than 5%; pass the mullite through 1~3mm, 0~1mm and 200 mesh sieves respectively, with the sieve residue less than 5%; package for standby use;

[0077] (2) Weigh the raw materials and their proportions in the above table, then put all the raw materials into a blender and stir for 20 minutes to fully mix the materials;

[0078] (3) After the materials are stirred evenly, continue to turn on the mixer and slowly add 6 parts by weight of water. After stirring until the castable becomes viscous, inject it into a 160mm×40mm×40mm mold and vibrate on a compaction table for 2 minutes to remove bubbles and compact the material.

[0079] (4) The castable obtained in step (3) is naturally cured for 24 hours and then demolded, and then baked in an oven at 110°C for 24 hours. After baking, three specimens are taken and heated at 1500°C for 3 hours, kept warm for 3 hours, and taken out as the furnace temperature naturally cools to room temperature to obtain a sample of high-performance rare earth composite calcium carbide furnace cover refractory castable.

[0080] Comparative Example 1

[0081] In Comparative Example 1, except that lanthanum oxide is not added, the other components and contents are the same as those in Example 1.

[0082] Comparative Example 2

[0083] In Comparative Example 2, except that lanthanum oxide is not added, the other components and contents are the same as those in Example 2.

[0084] Comparative Example 3

[0085] In Comparative Example 3, except that cerium oxide is not added, the other components and contents are the same as those in Example 3.

[0086] Comparative Example 4

[0087] In Comparative Example 4, except that no silicon oxide powder is added, the other components and contents are the same as those in Example 1.

[0088] Comparative Example 5

[0089] The brown corundum in Comparative Example 5 is replaced by high-purity magnesia, and the remaining components and contents are the same as those in Example 1.

[0090] Comparative Example 6

[0091] In Comparative Example 6, no aluminate cement is added, and the remaining components and contents are the same as those in Example 1.

[0092] Comparative Example 7

[0093] In Comparative Example 7, except for not adding clay additive, the other components and contents are the same as those in Example 1.

[0094] Table 8 Specific test data of Examples 1-5 and Comparative Examples 1-7

[0095] 110℃ flexural strength (MPa) 110℃ compressive strength(MPa) <![CDATA[Volume density at 110°C (g / cm 3 )]]> 1500℃ flexural strength (MPa) 1500℃ compressive strength (MPa) 1500℃ Linear change rate (%) Thermal shock resistance Example 1 11.5 72.5 3.02 14.8 102.3 -0.15 57 Example 2 12.0 76.8 3.05 15.6 109.6 -0.21 55 Example 3 12.5 81.2 3.06 16.8 113.5 -0.20 58 Comparative Example 1 9.8 67.9 2.92 10.8 92.1 -0.29 42 Comparative Example 2 10.1 66.8 2.93 11.5 91.2 -0.31 45 Comparative Example 3 9.7 65.9 2.91 11.0 95.8 -0.39 40 Comparative Example 4 11.2 72.8 3.02 12.4 97.2 -0.15 57 Comparative Example 5 11.0 71.9 3.01 12.8 93.5 -0.16 57 Comparative Example 6 10.9 71.5 3.03 13.8 101.3 -0.59 56 Comparative Example 7 11.1 70.8 3.02 14.2 102.6 -0.61 56

[0096] It can be seen from Table 8 above that, from Examples 1, 2, 3 and Comparative Examples 1, 2, 3, it can be seen that compared with the castable without adding lanthanum cerium oxide, the volume density of the castable with lanthanum cerium oxide added in the present invention increases, indicating that the addition of lanthanum cerium oxide can increase the volume density of the castable. In addition, it can be seen that compared with the castable without adding lanthanum cerium oxide, the flexural and compressive strength of the castable with lanthanum cerium oxide added in the present invention after sintering at 1500°C is significantly improved, indicating that the addition of lanthanum cerium oxide can improve the high-temperature flexural and compressive strength of the castable. In addition, it can be seen from Example 1 and Comparative Example 4 that after not adding silica powder, the high-temperature flexural and compressive strengths in Comparative Example 4 decrease to a certain extent compared with Example 1, indicating that the silica powder participates in the reaction of rare earth oxides to improve the high-temperature flexural and compressive strengths of the castable; it can be seen from Example 1 and Comparative Example 5 that after not adding brown corundum, the high-temperature flexural and compressive strengths in Comparative Example 5 are significantly reduced compared with Example 1, indicating that brown corundum participates in the reaction of the system, which helps to improve the high-temperature flexural and compressive strengths of the castable; it can be seen from Example 1 and Comparative Examples 6 and 7 that after not adding aluminate cement or clay additives, the linear change rate after firing at 1500°C is significantly increased, indicating that the addition of aluminate cement and clay additives is beneficial to reducing the linear change rate of the castable.

[0097] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0098] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-performance rare earth composite calcium carbide furnace cover refractory castable, characterized in that: The method is composed of the following raw materials in parts by weight: 100 parts of casting mixture, 0.5-3 parts of rare earth oxide, 0.1-0.2 parts of explosion-proof fiber, 0.1-0.3 parts of water reducing agent and 5-8 parts of water; The casting mixture is composed of the following raw materials in parts by weight: 50-68 parts of brown corundum, 15-20 parts of mullite, 5-10 parts of aluminate cement, 4-7 parts of alumina powder, 4-6 parts of silicon oxide powder, 3-5 parts of clay additive, and 1-2 parts of chromium oxide green; In the brown corundum raw material, the raw material with a particle size of 5-8 mm accounts for 10wt%-30wt% of the total amount of brown corundum, the raw material with a particle size of 3-5 mm accounts for 30wt%-35wt% of the total amount of brown corundum, the raw material with a particle size of 1-3 mm accounts for 15wt%-20wt% of the total amount of brown corundum, the raw material with a particle size of 0-1 mm accounts for 15wt%-20wt% of the total amount of brown corundum, and the raw material with a particle size of 200 mesh accounts for 10wt%-15wt% of the total amount of brown corundum; In the mullite raw material, the raw material with a particle size of 1-3 mm accounts for 30wt%-35wt% of the total amount of mullite, the raw material with a particle size of 0-1 mm accounts for 30wt%-35wt% of the total amount of mullite, and the raw material with a particle size of 200 mesh accounts for 30wt%-40wt% of the total amount of mullite; The rare earth oxide is lanthanum oxide, cerium oxide or a mixture of the two.

2. The high-performance rare earth composite calcium carbide furnace cover refractory castable according to claim 1, characterized in that: The type of aluminate cement is one of CA50, CA70 and CA80 or a mixture of several of them.

3. The high-performance rare earth composite calcium carbide furnace cover refractory castable according to claim 1, characterized in that: The clay additive is bentonite, Guangxi white mud or a mixture of the two.

4. The high-performance rare earth composite calcium carbide furnace cover refractory castable according to claim 1, characterized in that: The water reducing agent is one or a mixture of sodium tripolyphosphate, sodium lignin sulfonate, sodium hexametaphosphate, and calcium lignin sulfonate.

5. A method for preparing a high-performance rare earth composite calcium carbide furnace cover refractory castable according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Screen brown corundum and mullite to the required particle size and package them for later use; (2) Weigh the raw materials and their proportions according to claim 1, then put all the raw materials except water into a blender and stir for 10 to 20 minutes to fully mix the materials; (3) After the materials are stirred evenly, continue to turn on the mixer and slowly add 5 to 8 parts of water. Stir until the castable becomes viscous to obtain the refractory castable for the calcium carbide furnace cover.

6. The method for preparing the high-performance rare earth composite calcium carbide furnace roof refractory castable according to claim 5, characterized in that: Step (1) specifically includes: Place brown corundum and mullite in an electric heating blast drying oven at 90°C to 110°C to dry them; The brown corundum is passed through 5~8mm, 3~5mm, 1~3mm, 0~1mm and 200 mesh sieves respectively, and the sieve residue is less than 5%; the mullite is passed through 1~3mm, 0~1mm and 200 mesh sieves respectively, and the sieve residue is less than 5%; and they are packaged for use.

Citation Information

Patent Citations

  • Electric furnace top central area furnace cover and preparation method thereof

    CN104402469A

  • Low-temperature curing abrasion-resistant pouring material

    CN104591757A

Cited By

  • Preparation method of electric arc furnace cover with gradient structure, low thermal conductivity and high erosion resistance

    CN122167176A